Interpretation of Total Field Aeromagnetic Data over Kainji South East Area. - Illo, Oliver Amechi (Obafemi Awolowo University, 2014)
The total field aeromagnetic data over Kainji South - East have been studied to delineate the basement structural features in the form of profile sections and isobaths maps. Geological appraisal of the area indicates that the main lithological unit is a sedimentary unit generally grouped as the Bida sandstone overlying the basement complex.